Guided Inquiry and Multirepresentation Integration in a Dynamic Fluids Module for Strengthening Critical Thinking - Milisa Milisa; Saiyidah Mahtari; Suyidno Suyidno (Universitas Lambung Mangkurat, 2026)
Students' critical thinking skills in dynamic, fluid materials are still considered low because the learning process generally takes place conventionally and is limited to verbal and mathematical presentations. This causes students to have difficulty understanding abstract concepts, analyzing phenomena, and drawing logical conclusions. This research aims to develop a guided inquiry and multirepresentation-based dynamic fluid teaching module as an innovative effort to strengthen critical thinking skills. The research results show that: (1) The teaching module is valid because the validation results for the lesson plan (3.40), teaching materials (3.40), student worksheets (3.40), and critical thinking test (3.63) meet the valid category; (2) The module is practical because the learning implementation score is 3.57, which is in the good category; and (3) The teaching module is effective because the N-gain scores for critical thinking and learning outcomes are 0.69 each, which is in the moderate category. Multirepresentation enables students to understand concepts through various forms of representation, allowing them to grasp ideas more effectively, while guided inquiry provides structured stages of scientific investigation that enrich the learning experience. The integration of these two strategies into a single teaching package becomes the main contribution of this research, as it has been shown to make physics learning more meaningful and simultaneously foster higher-order thinking skills. This finding indicates that teachers can utilize the module to strengthen contextual learning in line with the Merdeka Curriculum, as well as use it as a reference for developing innovative teaching materials for other abstract physics topics or by incorporating digital technology.